(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
In the current generation, Internet of Things (IOT) has an important role to play in each and every area. There are many applications of IOT. One of the most important and efficient applications is in Home Automation. Consider a scenario of a building caught on fire, where one need to evacuate people from an emergency exit. Here, the problem is that one does not know how many people are present inside the building in order to evacuate them. In such cases, home automation plays a very important role. Occupancy Detection is one such area where one can sense the presence of a people in a room or a building. One of the ways of achieving Occupancy Detection is by Indoor Sensing. This paper proposes how to attain count of people present inside a room or a building at particular instant of time with the help of Infrared (IR) Sensors, finds out current temperature of a room or a building using Temperature Sensor and also activates an alarm when the room is caught on fire with the usage of Smoke Sensor and Buzzer.